Effect of hormonal therapy on bone mineral density of breast cancer women - Hasan Mussttaf , Alaa; Abid Ibreheem , Hamid; Jabbar Hasan , Yusra (Diyala Journal of Medicine, 2024)
Background: Aromatase inhibitor (AI) was received by breast cancer women with estrogen receptor-positive. The estrogen is the main stimulator for receptor-positive breast cancer cells development and growth, the adjuvant hormone ablation targeting estrogen can decrease the likelihood of cancer recurrence and prolong cancer-free survival. Objective: To determine the effect of this therapy on bone mineral density of women who received it. Patients and Methods: It was identified 100 women with local or regional breast cancer diagnosed and who received AI therapy in the January 2022 to February 2023 from Baqubah teaching hospital/Oncology Centre. It was used DEXA scan to determine the bone minerals density of 50 women after different years from receiving hormonal therapy and other 50 breast cancer women before receiving hormonal therapy. Results: It was shown that there is a significant difference (p<0.0001) in the spine and hip density of breast cancer women who received AIs compare with the bone density of other breast cancer women who did not receive it. Conclusion: It can conclude that Als plays an essential role for osteoporosis that reduce the quality of health and increase the risk of fraction in the breast cancer women.